Cosmetic dermatology : products and procedures - Draelos, Zoe Kececioglu (Chichester, West Sussex ; Hoboken, NJ : Wiley Blackwell, 2016)
Back for a new edition, Zu Draelos' outstanding resource to cosmetic dermatology again provides a highly-illustrated, clinical guide to the full range of cosmetic skin treatments.Bringing together experts from research, industry, surgery and practice, it is structured in four distinct parts for easy navigation by the busy clinician:Basic Concepts - giving an overview of the physiology pertinent to cosmetic dermatology and the delivery systems by which treatments can take effect;Hygiene Products - evaluating cleansing and moisturising products;Adornment - looking at aesthetic techniques such as cosmetics, nail protheses and hair treatment;Antiaging - ie, injectables, resurfacing and skin contouring techniques, and the rapidly growing area of Cosmeceuticals.With over 300 high-quality images and key summary boxes throughout, this new edition incorporates the newest procedural innovations in this rapidly developing field. Perfect for all dermatologists, especially those specialising in cosmetic dermatology and whether hospital-based or in private practice, it provides the complete cosmetic regimen for your patients and will be an indispensable tool to consult over and over again.
PART II Hygiene ProductsSection 1 Cleansers; CHAPTER 9 Bar Cleansers; Introduction; Impact of cleansing bars on skin structure and function; Studies comparing mildness properties of soap and syndet cleansing bars; Practical implications of mild cleansing for patients with common skin disease; The future of cleansing bars; Conclusions; References; CHAPTER 10 Personal Cleansers: Body Washes; Background; Types of body wash; Major formula components of body washes; In-use performance considerations for body washes; Who will benefit from using body washes?; Conclusions; References
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Skin -- Care and hygiene; Cosmetics; Dermatology; FAMILY & RELATIONSHIPS -- General; Cosmetics; Dermatology; Skin -- Care and hygiene; Medical; Cosmetics; Dermatologic Agents; Cosmetic Techniques; Dermatologic Surgical Procedures; Skin Care -- methods; Electronic books; Electronic books